A Success Story Leading Us to Think Big! - Kamboj, Jasmine; Kamboj, Rahul; Shah, Tejas; Khosla, Pam (Case Reports in Hematology, 2011)
Immune dysregulation is the hallmark of all autoimmunediseases. It is extremely interesting to study the associationsand pathogenesis of the various autoimmune diseases, likethe link between the AIHA and CLL. This link is wellestablished and is based on the fact that there is loss oftolerance to the self-antigen, which in turn leads to immunebasedhemolytic anemia. Around 30% of the patientswith CLL are at the risk of developing AIHA, and 11%eventually develop AIHA. Whether there is any definitelinkup between the corrupted immune system and “acute”leukemias/lymphomas is yet to be established. Needless tosay, if there was an association between the pathogenesis ofthe ALLs and AIHA, it would be a landmark in the field ofoncology as it would enforce early diagnosis and treatmentfor the disease which is much more aggressive and foundin a comparatively younger age group (predominantly inchildren and a mean age of 40 years in adults) as comparedto its chronic counterparts. The AIHA would serve as a “tip to the underlyingiceberg” in these situations, warning us of the crypticdiagnosis.